Bone sialoprotein‐αvβ3 integrin axis promotes breast cancer metastasis to the bone. Issue 10 (5th September 2019) - Wang, Li; Song, Lijie; Li, Juan; Wang, Yan; Yang, Chuanhong; Kou, Xiaomei; Xiao, Bin; Zhang, Wei; Li, Linhai; Liu, Shuwen; Wang, Jie
Abstract: The underlying mechanisms of breast cancer cells metastasizing to distant sites are complex and multifactorial. Bone sialoprotein (BSP) and αvβ3 integrin were reported to promote the metastatic progress of breast cancer cells, particularly metastasis to bone. Most theories presume that BSP promotes breast cancer metastasis by binding to αvβ3 integrin. Interestingly, we found the αvβ3 integrin decreased in BSP silenced cells (BSPi), which have weak ability to form bone metastases. However, the relevance of their expression in primary tumor and the way they participate in metastasis are not clear. In this study, we evaluated the relationship between BSP, αvβ3 integrin levels, and the bone metastatic ability of breast cancer cells in patient tissues, and the data indicated that the αvβ3 integrin level is closely correlated to BSP level and metastatic potential. Overexpression of αvβ3 integrin in cancer cells could reverse the effect of BSPi in vitro and promote bone metastasis in a mouse model, whereas knockdown of αvβ3 integrin have effects just like BSPi. Moreover, The Cancer Genome Atlas data and RT‐PCR analysis have also shown that SPP1, KCNK2, and PTK2B might be involved in this process. Thus, we propose that αvβ3 integrin is one of the downstream factors regulated by BSP in the breast cancer‐bone metastatic cascade. Abstract : In this study, we evaluated the relationship between bone sialoprotein (BSP), αvβ3 integrin levels, and the metastatic ability of breast cancer cells in patient tissues, and the data indicated that αvβ3 integrin level is closely correlated to BSP level and metastatic potential. Overexpression of αvβ3 integrin in cancer cells could reverse the effect of BSPi in vitro and in a mouse model, whereas knockdown of αvβ3 integrin has effects similar to BSPi. Moreover, The Cancer Genome Atlas data and RT‐PCR analysis show that SPP1, KCNK2, and PTK2B might be involved in this process. Thus, we propose that αvβ3 integrin is one of the downstream factors regulated by BSP in the breast cancer metastatic cascade.